Posted by **Ashley** on Friday, March 29, 2013 at 6:43pm.

Show that (P → Q) ↔ (¬P ∨ Q) in fitch

## Answer This Question

## Related Questions

- chemical reaction engineering - Propane steam reforming over an alumina ...
- Philosophy - HELP - How would you construct a proof to show that the following ...
- Philosophy - How would you construct a proof to show that the following ...
- Math! - Hi, How would you go about showing that the proposition below is a ...
- Discrete Math! - Hi, How would you go about showing that the proposition below ...
- Chem - At 298 K, Pb(IO3)2(s) ↔ Pb2+(aq) + 2IO3-(aq) Ksp = 2.6x 10-13 Pb2+(...
- Logic - Given the premises (p ⇒ q) and (r ⇒ s), use Propositional ...
- chemistry - Write both Kc and kp for the following reversible reactions: (wdp pg...
- Math - Construct a truth table for the statement. (p ↔ q) → p
- Math - Construct a truth table for the statement. (p ↔ q) → p

More Related Questions